Glossing an argument: Reformulation and exemplification in L2 Master’s theses - Guziurová Tereza (Topics in Linguistics, 2022)
Following a large body of research on metadiscourse in academic writing, this paper explores one feature of textual metadiscourse, code glosses, in English L2 academic texts written by Czech university students. The study draws on Hyland’s metadiscourse model (2005), which characterizes code glosses as devices that elaborate propositional meanings by rephrasing or explaining what has been said. Thus, they can help readers understand the writer’s intended meaning or contribute to the formation of persuasive arguments. The corpus consists of 48 English L2 Master’s theses representing three disciplines – linguistics, literature and English language teaching (ELT) methodology, totalling almost 950,000 words. The results are compared with professional writing represented by English L1 research articles from the same disciplines. The findings reveal differences in the frequency and functions of several code glosses, as novice writers are shown to overuse certain devices. The findings also indicate cross-disciplinary variation, as reformulation and exemplification proved to be much more prominent in linguistics and methodology than in literary studies.